Amino-functionalized MOFs (Metal-Organic Frameworks) composite heat stabilizer as well as preparation method and application thereof
Through the use of amino-functionalized MOFs composite thermal stabilizer, the pore structure of MOFs and the crosslinking reaction of zinc stearate, the environmental protection, toxicity and cost problems of existing PVC thermal stabilizers are solved, and the efficient thermal stability of PVC materials is achieved. Sex and safety.
Patent Information
- Application Number
- CN202411521625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Existing PVC thermal stabilizers have environmental problems, high toxicity and high cost, which are difficult to promote in price-sensitive applications. Traditional stabilizers may lead to product performance degradation and health risks under high temperatures or long-term use.
Using amino-functionalized MOFs composite thermal stabilizer, the adsorption and neutralization of PVC processing process through the combination of amino-functionalized protonated MOFs, zinc stearate and polyols. HCl in the process improves the thermal stability of PVC.
It significantly improves the thermal stability of PVC materials, with a thermal stability time of ≥45min, avoiding the performance and health risks of the products under high temperature or long-term use, and at the same time reducing costs and meeting environmental protection requirements.
Smart Images

Figure CN119463507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an amino-functional MOFs composite thermal stabilizer and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a widely used synthetic resin material. Due to its excellent chemical resistance, electrical insulation, wear resistance and molding processability, it is widely used in building materials, electronics, automobiles, packaging and other fields. However, PVC is easily affected by heat and light during processing and use, resulting in decomposition, discoloration and performance degradation. Therefore, the application of heat stabilizers is crucial to ensure the quality and durability of PVC products.
[0003] The main function of PVC heat stabilizer is to prevent or delay the thermal degradation of PVC during heating processing and long-term use. Traditional heat stabilizers include metal soap compounds such as lead salts, barium zinc, cadmium zinc, as well as organic tin and rare earth stabilizers. These heat stabilizers are indeed effective in practical applications, but due to increasingly stringent environmental regulations and people's concern about health and environmental protection, lead salt heat stabilizers are gradually being eliminated. Although organic tin stabilizers are more environmentally friendly than lead stabilizers, they still have certain toxicity. In addition, organic tin compounds may migrate to the surface or precipitate from PVC materials during use, especially under high temperature or long-term use conditions, resulting in decreased product performance and potential health risks. Compared with traditional lead salts and organic tin stabilizers, rare earth environmentally friendly stabilizers are often more expensive, which may affect their promotion in some price-sensitive applications. Therefore, the development of environmentally friendly and efficient PVC heat stabilizers has become a technical problem that needs to be solved urgently.
[0004] CN 115010947 A discloses a polyvinyl chloride stabilizer and its preparation method and application. Under alkaline conditions, small molecules containing functional groups are grafted onto metal organic framework materials through diacyl chloride. The stabilizer prepared has a stability time of about 30 minutes. The preparation process of the stabilizer is complicated, and its stability time can be further improved. Summary of the invention
[0005] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide an amino-functional MOFs composite thermal stabilizer.
[0006] Another object of the present invention is to provide an application of an amino-functional MOFs composite thermal stabilizer in the preparation of PVC materials.
[0007] Another object of the present invention is to provide a PVC pipe material.
[0008] Another object of the present invention is to provide a PVC pipe.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated MOFs, 20-30 parts of zinc stearate, and 10-15 parts of polyol;
[0011] The amino-functionalized protonated MOFs is at least one of amino-functionalized protonated UiO-66, MIL-101, MOF-5, and ZIF-8.
[0012] The present invention adopts amino-functionalized protonated MOFs, zinc stearate and polyol to prepare a composite thermal stabilizer. Since MOFs have a large specific surface area and many structural pores, the gas can be bound in the framework pores by intermolecular forces. Therefore, the composite thermal stabilizer is used to prepare PVC materials. Amino-functionalized protonated MOFs can adsorb HCl generated during the processing of PVC, and the amino groups on the ligands are protonated to form -NH3 + , can form hydrogen bonds or electrostatic interactions with HCl, or undergo ion exchange reactions to generate -NH3Cl; secondly, the inner surface of the pores of MOFs after protonation carries positive charges or acidic groups, which can better selectively adsorb polar molecules HCl, thereby improving the thermal stability of PVC.
[0013] Zinc stearate as a heat stabilizer for PVC will undergo the following reactions: (1) Capturing HCl: Zinc heat stabilizer can react with HCl and can inhibit the degradation of PVC by HCl to a certain extent; (2) Cross-linking reaction: Conjugated double bonds are produced during the decomposition of PVC. Double bonds are easily attacked by external factors such as heat, light, and oxygen, forming highly active free radicals, which can cause material degradation and discoloration, thereby causing the thermal stability of PVC materials to decrease. Zinc stearate can undergo cross-linking reaction with the conjugated double bonds in the material, making the material structure more stable. This cross-linking effect helps to improve the heat resistance and mechanical properties of the material.
[0014] ZnCl2 generated during the reaction of zinc stearate and hydrogen chloride has certain catalytic activity, which may further accelerate the degradation of PVC and cause the material to change color. This is because zinc chloride promotes the dehydrochlorination reaction of PVC to form a conjugated double bond system, making the material yellow or brown. Amino-functional MOFs can absorb most of the hydrogen chloride generated by decomposition, reduce the occurrence of this reaction, and effectively improve the thermal stability of PVC. Polyols, as auxiliary stabilizers, can form complexes with zinc chloride to reduce free zinc chloride in the system.
[0015] It should be noted that zinc stearate can also be used as an external lubricant to reduce the friction between molecular chains and between PVC and processing equipment during PVC processing, thereby reducing frictional heat generated during processing. This lubrication effect helps avoid premature decomposition of PVC and improves the initial thermal stability of the PVC system.
[0016] It should be noted that the amino-functionalized protonation in the present invention refers to firstly functionalizing the MOFs material with amino groups and then protonating it.
[0017] Preferably, the amino-functionalized protonated MOFs is amino-functionalized protonated UiO-66.
[0018] The hydrothermal stability and chemical stability of the traditional MOFs structure are relatively low. The UiO-66 used in the present invention has outstanding hydrothermal stability and chemical stability, and its crystal structure can remain stable at 500°C.
[0019] More specifically, the amino functionalization includes replacing the organic ligand of UiO-66, MIL-101 or MOF-5 with an organic ligand having an amino group, or modifying ZIF-8 with an organic amine.
[0020] More specifically, the organic ligand having an amino group is at least one of 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, and 2,3-diaminoterephthalic acid.
[0021] More specifically, the organic amine is at least one of ethylenediamine, 1,3-propylenediamine, and 1,4-butylenediamine.
[0022] More specifically, the organic amine modification of ZIF-8 comprises the following steps:
[0023] After vacuum activation, ZIF-8 is placed in saturated vapor of ethylenediamine, then added into an aqueous solution of ethylenediamine, separated and dried to obtain amino-functionalized ZIF-8.
[0024] Specifically, the acid used for the protonation is at least one of phosphoric acid, formic acid and acetic acid.
[0025] More specifically, the protonation comprises the following steps:
[0026] The amino-functionalized MOFs are placed in an acid solution, stirred, separated and dried to obtain the amino-functionalized protonated MOFs.
[0027] Preferably, the polyol is at least one of pentaerythritol, pentaerythritol distearate and pentaerythritol monostearate.
[0028] Specifically, the preparation method of the composite thermal stabilizer comprises the following steps:
[0029] The amino-functionalized protonated MOFs, zinc stearate and polyol are uniformly mixed to obtain the amino-functionalized MOFs composite thermal stabilizer.
[0030] The present invention also protects the use of an amino-functional MOFs composite stabilizer in the preparation of PVC materials.
[0031] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5-15 parts of inorganic filler, 3-8 parts of composite heat stabilizer, 1-2 parts of lubricant and 1-5 parts of processing aid.
[0032] Specifically, the inorganic filler is at least one of calcium carbonate, talc and silica powder.
[0033] Specifically, the lubricant is at least one of paraffin, stearic acid and polyethylene wax.
[0034] Specifically, the processing aid is at least one of MBS (methyl methacrylate-butadiene-styrene copolymer), CPE (chlorinated polyethylene), and POE (ethylene-octene copolymer).
[0035] Specifically, the preparation method of the PVC pipe material comprises the following steps:
[0036] The polyvinyl chloride, inorganic filler, the composite heat stabilizer, lubricant and processing aid are uniformly mixed to obtain the PVC pipe material.
[0037] A PVC pipe material comprises the PVC pipe material.
[0038] The preparation method of the PVC pipe comprises the following steps:
[0039] The PVC pipe material is melted, extruded and shaped to obtain the PVC pipe material.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The amino-functionalized protonated MOFs stabilizer provided by the present invention utilizes the characteristics of large specific surface area and multiple structural pores of MOFs to adsorb HCl and -NH3 generated during the processing of PVC. + It forms hydrogen bonds or electrostatic interactions with HCl, or undergoes ion exchange reactions to generate -NH3Cl; the inner surface of the pores of MOFs after protonation carries positive charges or acidic groups, which can better selectively adsorb polar molecules HCl; zinc stearate inhibits the degradation of HCl on PVC by reacting with HCl and undergoing cross-linking reactions with PVC; ZnCl2 generated during the reaction of zinc stearate and hydrogen chloride complexes with polyols, and the three work together to improve the thermal stability of PVC.
[0042] The PVC material prepared by using the amino-functional MOFs stabilizer provided by the present invention has excellent thermal stability, and the thermal stability time is ≥45 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The figure is a torque rheometer test result diagram of the embodiment and the comparative example. DETAILED DESCRIPTION
[0044] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0045] Polyvinyl chloride: Manufacturer: Xinjiang Zhongtai (Group) Co., Ltd., Model: SG-5.
[0046] The preparation method of amino-functionalized UiO-66 comprises the following steps:
[0047] Add N,N-dimethylformamide (DMF), deionized water and glacial acetic acid to the lining, stir evenly, add ZrCl4, stir for 10 minutes to obtain a mixed solution A; prepare a 0.4M 2-aminoterephthalic acid / DMF solution, recorded as solution B; add solution 2 to solution 1, stir for 1 hour, and then put it into the lining of the hydrothermal reactor, and put the reactor in an oven at 110°C for 48 hours; after the reaction is completed, put the obtained suspension into a centrifuge and pour out the supernatant; add DMF for washing, repeat the centrifugal separation operation 3 times, then wash with acetone, put the sample in an oven at 100°C and dry for 8 hours to obtain UiO-66.
[0048] The preparation method of UiO-66 is the same as that of amino-functionalized UiO-66, except that solution B is 0.3 M terephthalic acid / DMF.
[0049] The preparation methods of amino-functionalized MIL-101 and amino-functionalized MOF-5 are similar to the above methods. In the specific implementation of the present invention, the metal ion of amino-functionalized MIL-101 is Cr 3+ The metal center of amino-functionalized MOF-5 is Zn 2+ .
[0050] The preparation method of amino-functionalized ZIF-8 comprises the following steps:
[0051] S1. Dissolve zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in deionized water to prepare a zinc nitrate solution; then, dissolve 2-methylimidazole in another 160g of deionized water to prepare a 2-methylimidazole solution. The two solutions were vigorously stirred at room temperature, and the mixed colorless solution immediately turned milky white. After 20 minutes of stirring, the synthesized ZIF-8 particles were collected by centrifugation (9000r / min, 10 minutes) and washed three times with deionized water.
[0052] S2. The synthesized ZIF-8 particles were dried at 50°C for 12 hours and vacuum activated at 150°C for 1 hour. They were then placed in saturated vapor of ethylenediamine (EDA) for 3 hours, and then added to a 25% EDA aqueous solution and reacted at 117°C for 2 hours. Afterwards, the aminated ZIF particles were collected after centrifugation (9000r / min, 10 minutes), washed three times with deionized water, and completely dried in a vacuum oven at 50°C for 12 hours.
[0053] The preparation method of protonated MOFs includes the following steps:
[0054] The prepared aminated MOFs were placed in a 1M phosphoric acid solution and stirred at 60°C for 24 hours. After the reaction was completed, the desired solid was obtained by centrifugation, and then the solid was washed with ethanol until the washing solution was neutral. The washed sample was vacuum dried at 60-80°C, or dried in air until the sample was completely dehydrated.
[0055] The preparation method of amino-functional MOFs composite thermal stabilizer comprises the following steps:
[0056] The raw material components are mixed evenly to obtain the amino-functional MOFs composite thermal stabilizer.
[0057] The preparation method of PVC pipe material comprises the following steps:
[0058] Add all raw material components into a high-speed mixer and mix them evenly to obtain PVC pipe material.
[0059] The preparation method of PVC pipe comprises the following steps:
[0060] The obtained PVC pipe material is added into a screw extruder, and the PVC pipe material is obtained after melt extrusion and mold shaping.
[0061] Example 1
[0062] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated UiO-66, 20 parts of zinc stearate, and 10 parts of pentaerythritol.
[0063] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 8 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0064] Example 2
[0065] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated UiO-66, 25 parts of zinc stearate, and 10 parts of pentaerythritol.
[0066] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 8 parts of calcium carbonate, 4 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0067] Example 3
[0068] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated MIL-101, 30 parts of zinc stearate, and 15 parts of pentaerythritol.
[0069] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 15 parts of calcium carbonate, 4 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 2.5 parts of MBS.
[0070] Example 4
[0071] The specific components and preparation method of an amino-functional MOFs composite thermal stabilizer are the same as those in Example 1.
[0072] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 6 parts of MOFs composite heat stabilizer, 1.5 parts of paraffin wax and 2.5 parts of MBS.
[0073] Example 5
[0074] The specific components and preparation method of an amino-functional MOFs composite thermal stabilizer are the same as those in Example 2.
[0075] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 6 parts of MOFs composite heat stabilizer, 1.5 parts of paraffin wax and 3 parts of MBS.
[0076] Example 6
[0077] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated ZIF-8, 25 parts of zinc stearate, and 15 parts of pentaerythritol.
[0078] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 5 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 2.5 parts of MBS.
[0079] Example 7
[0080] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated MOF-5, 25 parts of zinc stearate, and 15 parts of pentaerythritol.
[0081] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 5 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 2.5 parts of MBS.
[0082] Comparative Example 1
[0083] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated UiO-66, 25 parts of zinc stearate, and 5 parts of pentaerythritol.
[0084] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 6 parts of calcium carbonate, 4 parts of MOFs composite heat stabilizer, 1 part of paraffin wax and 3.5 parts of MBS.
[0085] Comparative Example 2
[0086] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated UiO-66, 5 parts of zinc stearate, and 12 parts of pentaerythritol.
[0087] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5 parts of calcium carbonate, 5 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 2.5 parts of MBS.
[0088] Comparative Example 3
[0089] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional protonated UiO-66, 40 parts of zinc stearate, and 10 parts of pentaerythritol.
[0090] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of calcium carbonate, 6 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0091] Comparative Example 4
[0092] An amino-functional MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of amino-functional UiO-66, 25 parts of zinc stearate, and 10 parts of pentaerythritol.
[0093] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of calcium carbonate, 8 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0094] Comparative Example 5
[0095] A heat stabilizer comprises the following components in parts by weight: 100 parts of zinc stearate and 50 parts of pentaerythritol.
[0096] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of calcium carbonate, 8 parts of a heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0097] Comparative Example 6
[0098] A proton functionalized MOFs composite thermal stabilizer comprises the following components in parts by weight: 100 parts of protonated UiO-66, 20 parts of zinc stearate, and 10 parts of pentaerythritol.
[0099] A PVC pipe material comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of calcium carbonate, 5 parts of MOFs composite heat stabilizer, 2 parts of paraffin wax and 3 parts of MBS.
[0100] Performance Testing
[0101] The heat resistant stability time test was performed on the PVC pipe materials in the embodiment and the comparative example, and the specific method is as follows:
[0102] (1) Torque rheometer test method: A torque rheometer is used to conduct rheological experiments on PVC pipe materials. The test temperature is 185°C and the rotation speed is 27 rpm. Samples are taken at regular intervals and their color changes are observed using a colorimeter. The time it takes for the color to change from colorless to yellow is the thermal stability time.
[0103] (2) Congo red method: According to GB / T 2917.1-2002 Congo red method for determination of hydrogen chloride and any other acidic products released by blends and products based on homopolymers and copolymers of vinyl chloride at high temperatures, the test temperature is 200°C. The HCl gas generated during the decomposition of PVC reacts with the Congo red test paper, causing the test paper to change color. By measuring the time required for the test paper to change color, the thermal stability of PVC can be evaluated.
[0104] It should be noted that the principles of the two testing methods are different. The Congo red method mainly tests the hydrogen chloride produced by the decomposition of the material, while the torque rheometer tests the color of the actual sample. This color change is mainly due to the unsaturated double bonds generated by the decomposition of PVC, which will make the material turn yellow.
[0105] Specific test results are as follows Figure 1 As shown in Table 1:
[0106] Table 1 Congo red test results
[0107] Thermal stability time / min Example 1 51 Example 2 46 Example 3 47 Example 4 47 Example 5 49 Example 6 45 Example 7 46 Comparative Example 1 36 Comparative Example 2 31 Comparative Example 3 25 Comparative Example 4 40 Comparative Example 5 12 Comparative Example 6 15
[0108] Combined with the torque rheometer test results and the Congo red method test results, the thermal stability time of the composite thermal stabilizer prepared by the present invention is more than 45 minutes, and it has excellent thermal stability. It can be seen from Example 2 and Comparative Example 4 that the protonated amino group on the ligand can react with hydrogen chloride, which can effectively improve the long-term thermal stability of PVC pipes. From the test results of Comparative Example 4 and Example 2, it can be seen that the thermal stability of unprotonated MOFs is good, but there is still a certain gap compared with the protonated MOFs. The difference in performance between the two may be due to the different binding forces of the two for hydrogen chloride. The unprotonated MOFs fix hydrogen chloride by van der Waals force, while the protonated MOFs fix hydrogen chloride in the pores of MOFs by electrostatic attraction.
[0109] It can be seen from Example 1 and Comparative Example 5 that there is no amino-functionalized protonated MOFs in the thermal stabilizer, and the thermal stability of the PVC material is poor, which shows that the amino-functionalized protonated UiO-66 can greatly improve the thermal stability of the PVC material.
[0110] From the test results of Example 2, Comparative Example 2 and Comparative Example 3, it can be seen that protonated UiO-66-NH2 can effectively absorb the hydrogen chloride gas generated during the processing of PVC and improve the thermal stability of the material. However, too much zinc stearate will cause the side reaction to generate ZnCl2, which will accelerate the decomposition of PVC, and too little zinc stearate will lead to poor initial thermal stability of the polymer. This shows that zinc stearate has a great influence on the initial thermal stability of the entire system, so it is necessary to control the proportion of zinc stearate in the composite thermal stabilizer.
[0111] It can be seen from Comparative Example 6 and Example 2 that simply protonating MOFs does not improve the thermal stability of the system. This may be because the selected MOFs do not have suitable sites to supply protons, so the protonation effect is not good.
[0112] From the test results of Comparative Example 1 and Example 2, it can be seen that a low content of pentaerythritol will affect the thermal stability of the PVC material. This is because pentaerythritol can effectively complex the ZnCl2 produced by the side reaction, reduce the free ZnCl2 in the system, and thus inhibit the decomposition of the PVC material.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An amino-functional MOFs composite thermal stabilizer, characterized in that: The method comprises the following components in parts by weight: 100 parts of amino-functionalized protonated MOFs, 20-30 parts of zinc stearate, and 10-15 parts of polyol; The amino-functionalized protonated MOFs is at least one of amino-functionalized protonated UiO-66, MIL-101, MOF-5, and ZIF-8.
2. The composite heat stabilizer according to claim 1, characterized in that: The amino functionalization includes replacing the organic ligand of UiO-66, MIL-101 or MOF-5 with an organic ligand having an amino group, or modifying ZIF-8 with an organic amine.
3. The composite thermal stabilizer according to claim 2, characterized in that: The organic ligand with an amino group is at least one of 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, and 2,3-diaminoterephthalic acid.
4. The composite thermal stabilizer according to claim 2, characterized in that: The organic amine is at least one of ethylenediamine, 1,3-propylenediamine and 1,4-butylenediamine.
5. The composite thermal stabilizer according to claim 1, characterized in that: The acid used for the protonation is at least one of phosphoric acid, formic acid and acetic acid.
6. The composite thermal stabilizer according to claim 1, characterized in that: The polyol is at least one of pentaerythritol, pentaerythritol distearate and pentaerythritol monostearate.
7. The composite thermal stabilizer according to claim 1, characterized in that: The preparation method of the composite thermal stabilizer comprises the following steps: The amino-functionalized protonated MOFs, zinc stearate and polyol are uniformly mixed to obtain the amino-functionalized MOFs composite thermal stabilizer.
8. Use of the amino-functional MOFs composite thermal stabilizer according to any one of claims 1 to 7 in the preparation of PVC materials.
9. A PVC pipe material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of polyvinyl chloride, 5-15 parts of inorganic filler, 3-8 parts of the composite heat stabilizer according to any one of claims 1 to 7, 1-2 parts of lubricant and 1-5 parts of processing aid.
10. A PVC pipe, characterized in that: The PVC pipe comprises the PVC pipe material as claimed in claim 9.
Citation Information
Patent Citations
Efficient zinc-based composite heat stabilizer for PVC (polyvinyl chloride) and preparation method thereof
CN103613884A
Hexadentate flexible benzimidazole zinc metal complex and application thereof in PVC heat stabilizer
CN104177299A
Water-stable microporous difunctional MOFs material as well as preparation method and application thereof
CN113912856A
Heat stabilizer for processing soft transparent PVC (polyvinyl chloride) and preparation method of heat stabilizer
CN114230941A
Metal / carbon nano composite fiber derived based on MOFs (Metal Organic Frameworks) as well as preparation method and application of metal / carbon nano composite fiber
CN114875525A
Cited By
Functionalized MOF composite material, preparation method thereof and application of functional MOF composite material in glabridin purification
CN120424361A
A functionalized MOF composite material, its preparation method, and its application in the purification of glycyrrhizin.
CN120424361B